What is the appropriate “first lymph node” in the era of segmentectomy for non-small cell lung cancer? - Seitlinger, Joseph; Stasiak, Florent; Piccoli, Juliette; Maffeis, Gabriele; Streit, Arthur; Wollbrett, Christophe; Siat, Joelle; Gauchotte, Guillaume; Renaud, Stéphane (Frontiers in Oncology, 2023)
Introduction: The place of segmentectomy in the management of lung cancer is shifting following the inspiring results of the Japanese JCOG0802 trial. In this study, authors suggested that performing segmentectomy would require in an optimal way an intraoperative confirmation of pN0 tumor with a frozen section. Our objective was to determine whether the proposed technique, i.e. adjacent lymph node analysis, is consistent with the results of our study on sentinel lymph node (SLN) detection using fluorescence. Methods: This is a retrospective, observational, single center study. Eighty-one patients with suspected localized stage NSCLC (IA to IIA) were included between December 2020 and March 2022. All patients received an intra-operative injection of indocyanine green (ICG) directly in the peritumoral area or by electromagnetic navigational bronchoscopy (ENB). The SLN was then assessed by using an infrared fluorescence camera. Results: In our cohort, SLN was identified in 60/81 patients (74.1%). In 15/60 patients with identified SLN (25%), NIR-guided SLN was concordant with the suggestions of JCOG0802 study. A retrospective SLN pathological analysis was performed in 43 patients/60 cases with identified SLN (71.2%), including 37 cases of malignant disease. Occult micro-metastases were found in 4 patients out of 37 SLN analyzed, leading to a 10.8% upstaging with NIR-guided SLN analysis. Conclusion: At the time of segmentectomies, ICG technique allowed the identification of the SLN in a high percent of cases and in some areas usually out of the recommended stations for lymph node dissection.